Positive impact of smartphone application: whatsapp & facebook for online business - Ibrahim, Jamaludin; Chee Ros, Rafidah; Sulaiman, Nurul Faatihah; Che Nordin, Roszaini; Li , Ze Yuan (IJSRP.ORG, 2014)
Science and technologies contribute to the development and improvement of various activities globally. One of those activities is a day to day business such as household selling; home based, kitchen needs and utilities, wedding door gifts and souvenirs, flower arrangements/bouquets, artworks, cloth, scarf and varieties of other products. In this paper we aim to explore the positive impact of the smartphone application for online business. The usage of smartphone applications such as WhatsApp and Facebook has contributed enormously to especially online business. Research has been conducted using informal interview, questionnaire, and online survey based on question develop by researcher. The respondents consist of 100 targeted participants which involves university students, housewives, and random public at various places. The outcome indicates that the smartphone application has given the positive impact to the online business which can help to develop business success.